FARMACOCINÉTICA Y BIODISPONIBILIDAD ABSOLUTA DE MARBOFLOXACINA EN BÚFALOS (Bubalus bubalis) (FAVE Sección Ciencias Veterinarias, 2021)
The aim of this study was to evaluate the pharmacokinetic behaviour and the absolute bioavailability of marbofloxacin (MFX) in adult water buffaloes and to estimate the pharmacokinetic parameters for calculating the therapeutic dose in this animal species. Six adult buffaloes (3 males and 3 females) where treated by intravenous (IV) and subcutaneous (SC) route with a 10% experimental MFX injectable formulation at the dose of 2 mg/kg. After administration blood samples were drawn at pre-established times and MFX plasma concentrations where determined by microbiologic method. The pharmacokinetic analysis was made by compartmental analysis. After IV administration MFX presented a clearance of 198.4 ± 21.0 mL.kg.h and a half-life of elimination of 7.64 ± 3.29 h. After SC administration marbofloxacin presented a half-life of elimination of 8.5 ± 2.42 h, reaching it maximum plasma concentration (1.67 ± 0.516 μg/mL) at 1.69 ± 0.231 h, with a bioavailability of 80.8 ± 11.2 %. The estimated values of clearance and bioavailability will be employed in further studies for calculating the therapeutic dose of MFX in water buffaloes.
Keywords: Marbofloxacina, Farmacocinética, Biodisponibilidad, Búfalos